Ferrocarriles, ciudades y estaciones en Portugal, de finales del siglo XIX al siglo XXI - Magda Pinheiro (Transportes, Servicios y Telecomunicaciones, 2019)
This Article aims to relate the construction of railway stations and urban planning theories and practices .Seeking a comparative approach its aim is to study the portuguese case from the end of nineteenth century until the beginning of the XXI century.